Bidirectional Network in Hybrid Coarse Wavelength Division Multiplexing/Time Division Multiplexing (CWDM/TDM) on NG-PON2 for 40 Gbps - Akhmad Hambali; Brian Pamukti (National Research and Innovation Agency, 2019)
In this research, we propose hybrid Coarse Wavelength Division Multiplexing/Time Division Multiplexing (CWDM/TDM)-Passive Optical Networks (PON) scheme for optimizing the new technology of Gigabit-PON (GPON) called Next Generation-PON Stage 2 (NG-PON2). The simulation of using this scheme proved that Q-Factor increase and Bit Error Rate (BER) decreased, significantly. We use CWDM scheme for downstream while TDM is used for upstream, and we assimilate both of them with new configuration in bidirectional cable setting. CWDM is used due to low nonlinearity effect like Kerr effects. It has the same working principle based on (Time Wavelength Division Multiplexing-PON) TWDM-PON by differentiating the use of wavelength, it can be easily implemented on existing PON technology, and can be used in single-mode optical fiber (SMF) with greater bandwidth and much cheaper operational costs. From the calculations and simulations, it can be analyzed that the network Hybrid of CWDM / TDM-PON able to work on bit rate of 40/10 Gbps on the number of users 32, 64, and 128, with Q-Factor value is above 6 equal to International Telecommunication Union of Telecommunication (ITU-T) standard. The number of users 32 with two cable lengths of 10 and 20 km have value of Q-Factor 25.960 and 14.815 respectively, while64 users with the same cable length have Q-Factor value of 15.808 and 13.046 respectively. In addition, 128 users with the same cable length have BER value of 17.778 and 12.944 respectively.